An abnormal mRNA produced by a novel PMP22 splice site mutation associated with HNPP. Issue 4 (30th September 2005) - Bellone, E; Balestra, P; Ribizzi, G; Schenone, A; Zocchi, G; Di Maria, E; Ajmar, F; Mandich, P
Abstract : Hereditary neuropathy with liability to pressure palsies (HNPP) is an autosomal dominant, demyelinating neuropathy. Point mutations in the PMP22 gene are a rare cause of HNPP. A novel PMP22 splice site mutation (c.179+1 G→C) is reported in an HNPP family. By reverse transcriptase-polymerase chain reaction experiments, this mutation was shown to cause the synthesis of an abnormal mRNA in which a premature stop codon probably produces a truncated non-functional protein.